2015
DOI: 10.3892/etm.2015.2383
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shenkang granules on the progression of chronic renal failure in 5/6 nephrectomized rats

Abstract: Abstract. Shenkang granules (SKGs) are a Chinese herbal medicinal formula, consisting of rhubarb (Rheum palmatum L.), Salvia miltiorrhiza, milkvetch root [Astragalus membranaceus (Fisch.) Bunge] and safflower (Carthamus tinctorius L.). The aim of the present study was to investigate the effect of SKG on chronic renal failure (CRF) in 5/6 nephrectomized (5/6 Nx) rats. The rats were randomly divided into seven groups (n=10 per group) as follows: (i) 5/6 Nx (model group; 2.25 ml/kg/day normal saline); (ii) SKGL (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…However, the molecular mechanism underlying the renoprotective effect of SK is rarely explored. In recent reports, SK has been found to protect against renal injury in animal models of 5/6 nephrectomy and STZ-induced DN through its antioxidant and antifibrotic potential [9,10]. In this study, we showed antiinflammatory and antiapoptotic effects of SK in TAC-induced renal injury.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…However, the molecular mechanism underlying the renoprotective effect of SK is rarely explored. In recent reports, SK has been found to protect against renal injury in animal models of 5/6 nephrectomy and STZ-induced DN through its antioxidant and antifibrotic potential [9,10]. In this study, we showed antiinflammatory and antiapoptotic effects of SK in TAC-induced renal injury.…”
Section: Discussionsupporting
confidence: 66%
“…There is overwhelming evidence demonstrating that, through its antifibrotic and antioxidant potential, SK can effectively preserve renal proximal tubule epithelial cell (HK-2 cell) viability, inhibit high-glucose-induced proliferation of renal mesangial cells, and protect against renal lesions [6-8]. The renoprotective effects of SK have also been reported in 5/6 nephrectomy [6,9], streptozotocin (STZ)-induced diabetic nephropathy (DN) [10], and spontaneously hypertensive nephropathy [11]. However, the beneficial effects of SK on TAC-induced nephropathy remain to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…The main experimental manifestations of these mice were proteinuria, hyperlipidemia, hypoproteinemia, hypoxemia and renal hypofunction (18,19). Accordingly, certain biochemical indices of the mice were altered, such as increased SCr, BUN, TG and UTP (20). In the present study, the associated biochemical indices (SCr, BUN, TC, TG, UTP, TP and Alb) were examined following establishment of the rat model, and the results agreed with those of previous reports (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, certain biochemical indices of the mice were altered, such as increased SCr, BUN, TG and UTP (20). In the present study, the associated biochemical indices (SCr, BUN, TC, TG, UTP, TP and Alb) were examined following establishment of the rat model, and the results agreed with those of previous reports (20,21). Together with the examination of general appearance and pathological sections of the mice, these results indicated that the renal system of rats in the GS group had swelling and fibrosis, their functions were severely impaired, and absorption and filtration capabilities were weakened.…”
Section: Discussionmentioning
confidence: 99%
“…1 Current clinical studies have demonstrated that SK injection could simultaneously reduce the levels of serum creatinine (Scr), total protein (U-TP), microalbumin (mALB), blood urea nitrogen (BUN) and increase the creatinine clearance rate (Ccr), nitric oxide (NO), albumin (Alb) serum levels, and then improve the clinical symptoms and delay the progress in patients. 2 Our previous chemical profile and quality analysis researches had found that SK injection contains gallic acid, danshensu, rosmarinic acid, salvianolic acid A, aloeemodin, rhein and emodin, which were considered as the main bioactive compounds. 3,4 However, up to now, many studies paid close attention to the pharmacological and chemical research of SK injection, but its pharmacokinetic behaviors and metabolism profiling are absent.…”
Section: Introductionmentioning
confidence: 99%